The impact of gendered product marketing on the purchasing decisions of Generation Z: A case study of Gillette. - Criticos, Emma (The IIE, 2022)
This small-scale, qualitative research study investigated the impact gendered product marketing has on the purchasing decisions of Generation Z, a generational cohort whose power and clout over brands is consistently increasing. The research is specifically focused on Gillette (a subsidiary of the house of brands, Procter & Gamble) and its two sub-brands, Gillette (for men) and Gillette Venus (for women). Gendered product marketing has been used by many brands and marketers as a strategic choice in order to differentiate and appeal directly to a specific consumer. Due to an everchanging social climate, members of the Generation Z cohort are starting to venture away from brands embracing stereotypical gendered product marketing. They are supporting brands that address social issues, confront gender stereotypes and resonate with their Generation Z values. Gillette is perceived as embracing gendered product marketing and needs to reconsider their strategies, including their brand identities and architecture, in order to maintain their current target audience whilst attracting the consumers of Generation Z, whose purchasing power is consistently increasing. The study utilised online questionnaires, focus groups and a semi-structured interview in order to gain an in-depth and holistic understanding of the gendered product marketing present within Gillette sub-brands and products, as well as the perceptions Generation Z consumers have towards gender-neutral products. The data gathered allowed for meaningful findings and recommendations to be identified, both of which can be utilised by Gillette, in their attempt to strategize and solidify their position in the mind of the Generation Z consumer. Overall, it was found that the Generation Z consumer is conscious of gendered product marketing within Gillette’s products and sub-brands and would be more inclined to purchase gender-neutral products as opposed to gendered products (if the choice was offered by Gillette), as inclusivity and equality is of utter importance to this cohort. These findings can serve as a guide for Gillette and other brands wanting to alter their strategies in order to attract Generation Z consumers through incorporating gender-neutral product marketing.
Keywords: Consumer behaviour; Brand image; Brand equity; Gender